2019
DOI: 10.1016/j.apnu.2019.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Affiliate stigma, perceived social support and perceived stress in caregivers of children with autism spectrum disorder: A multiple mediation study

Abstract: Background: Affiliate stigma negatively predicts social support, and positively predicts psychological distress, in caregivers of children with ASD. Whether the affiliate stigmadistress relationship occurs indirectly via social support however has not been explored. Methods: A correlational design was used. A sample of n=124 caregivers of children with ASD completed an online survey assessing affiliate stigma, perceived support from family, friends and significant others, and perceived stress. Results: The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
(38 reference statements)
1
9
1
Order By: Relevance
“…This research explored the relationship between these three variables and confirmed that social support is an important factor affecting sleep quality, and it also increases the mediating factor of social support on sleep quality. However, this is not consistent with the research results of high social support promoting perceived stress [32][33][34][35]. But it is consistent with the research that perceived stress has a positive effect on sleep quality [48,50].…”
Section: The Mediating Role Of Psychological Resilience and Perceived Stresscontrasting
confidence: 67%
See 1 more Smart Citation
“…This research explored the relationship between these three variables and confirmed that social support is an important factor affecting sleep quality, and it also increases the mediating factor of social support on sleep quality. However, this is not consistent with the research results of high social support promoting perceived stress [32][33][34][35]. But it is consistent with the research that perceived stress has a positive effect on sleep quality [48,50].…”
Section: The Mediating Role Of Psychological Resilience and Perceived Stresscontrasting
confidence: 67%
“…It is found that social support is negatively correlated with perceived stress [32][33][34][35]. Social support was negatively correlated with post-traumatic stress disorder (PTSD) [36,37].…”
Section: The Mediating Role Of Perceived Stressmentioning
confidence: 99%
“…One of the challenges parents of children with ASD face is the societal stigma directed towards their children and themselves ( Kinnear et al, 2016 ). Due to certain features of ASD–poor social skills, inappropriate affective expressions, self-destructive acts, and language impairments–people with a diagnosis of ASD are likely to experience stigmatizing reactions from the general public ( Butler & Gillis, 2011 ), such as insensitive comments, hostile stares, or even physical aggression ( Lovell & Wetherell, 2019 ). Previous research highlights that stigmatized individuals may develop self-stigma, defined as an internalized cognitive-affective self-directed and rigid process that results in the individuals agreeing with stigmatizing opinions and applying them to themselves ( Smith-Palmer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This experience often leaves parents feeling humiliated, isolated, and judged ( Broady, Stoyles & Morse, 2017 ), hence they may internalize the content of stigmatizing words and thoughts, and therefore social stigma can be transformed into self-stigma; when this happens, individuals seem to accept negative social judgments and incorporate them into their own value system ( Chan & Lam, 2018 ). In consequence, the development of negative self-thoughts intensifies, hence one’s self-esteem and self-efficacy may decrease, causing individuals to experience higher levels of stress and diminishing their well-being ( Corrigan, Rafacz & Rüsch, 2011 ; Lovell & Wetherell, 2019 ). Based on these factors, self-stigma may make caregiving responsibilities more difficult for parents and play a negative role in their relationship with the child ( Chan & Lam, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the effectiveness of such interventions will require parental/familial commitment to the programs in order to reap the full benefits, we believe that implementing such programs will be valuable for families who may be struggling and seeking additional support. Since families are likely spending more time together due to the pandemic guidelines, familial support and overall family dynamics can be especially vital in managing individuals with ASD, creating reduced perceived parent/caregiver stress [ 7 ] and positively impacting the family quality of life [ 8 ]. It is important, however, to ensure that these parent training approaches do not place additional pressure and burden on the parents/caregivers.…”
mentioning
confidence: 99%